Lope de Vega en las justas poéticas de 1622. Las comedias de san Isidro: simbología y estructura metafórica - Sánchez Jiménez, Antonio (Madrid: Iberoamericana, 2022)
Analysis of Lope de Vega's participation in the 1622 poetic jousts, and of the symbolism of the two plays that he wrote for the festivities.
Keywords: Lope de Vega; Golden Age Spanish Theater; San Isidro